ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI KEPUASAN PELANGGAN PADA LBB ANTOLOGI SEMARANG - Zaka, Amar Rizki; Sutopo, Sutopo (Faculty of Economics and Business Diponegoro University, 2017)
The purpose of this research are to know the factors that influence on LBB ANTOLOGI’s customer’s satisfaction and analyze the most dominant factor that influence on LBB ANTOLOGI’s customers’ satisfaction. Samples that used in this research are 100 amount of respondent and taken using purposive sampling approach which means taking sampling based on certain targets, criteria that used is parents who enroll their children for taking courses, at least one semester, in LBB ANTOLOGI Semarang. Based on the research result, can be summarized as followed :Independent variable that mostly affect the dependent variable is promotion variable (0,456), followed by price perception variable (0,359), and quality service variable (0,168). T test that used to examine the hypothesis shows that three used variables positively and significantly affect the dependent variables of customers’ satisfaction. The number that obtained from adjusted R square is 0,847, shows that 84,7% purchase decision are explained through price perception variable, service quality and promotion, while another 15,3% is affected by others variables that are not examined in this research.